Development and molecular characterization of doxorubicin-resistant canine mammary gland tumour cells - Sahabi, Kabiru; Selvarajah, Gayathri T.; Mokrish, Ajat; Rasedee, Abdullah; Kqueen, Cheah Y. (Taylor and Francis Group, 2022)
Canine mammary gland tumour (CMT) commonly affects the female dog. The objective of this study was to develop a doxorubicin-resistant CMT cell line and determine its in vitro and in vivo characteristics, including mRNA and microRNA (miRNA) expression profiles. Doxorubicin-resistant CMT-Star cells were developed from CMT-Stylo cells. The cells were characterized, including tumorigenicity in NOD/SCID mouse models. MiRNA and mRNA expression of the two cell lines were profiled and clustered. ATP binding cassette subfamily B member 1 (ABCB1) and subfamily G member 2 (ABCG2) expressions were significantly increased in the CMT-Star cell line. CMT-Star cells also had altered expression of 785 genes and 14 miRNAs. Downregulating plasminogen (PLG) and plasminogen activator urokinase (PLAU) while upregulating transforming growth factor beta receptor 3 (TGFBR3), epidermal growth factor receptor 1 (EGFR1) and ABCB1 rendered CMT-Star cells less proliferative, less invasive and more resistant to chemotherapeutic drugs. The upregulated miRNAs in CMT-Star cells include miRNA-191, -29a, -107, -99b, -874, -93 and -210, while the downregulated miRNAs include miRNAs-106a, -92a, -92b, -155 and -15b. TGFβR, EGF receptor 1 and Wnt signalling are enriched in doxorubicin-resistant CMT-Star cells and could be potential therapeutic targets in dogs with doxorubicin-resistant CMT.